1997
DOI: 10.5271/sjweh.218
|View full text |Cite
|
Sign up to set email alerts
|

Shift work, occupation and coronary heart disease over

Abstract: ObjectivesThe risk of coronary heart disease (CHD) in shift work and the possible pathways for CHD in industrial workers were studied along with the importance of shift work as an occupational class gradient of CHI) risk. Methods Data from a psychosocial questionnaire and on life-style factors, blood pressure, and serum lipid levels were used for a follow-up study of a cohort of 1806 workers. CHD was determined from official Fi~~nish registers. Cox's proportional hazards models were used with different covaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 166 publications
(16 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…Nevertheless, the descriptive results revealed that both industry and healthcare shift workers had a higher prevalence of emotionally and physically demanding work compared to day workers employed in the same sector. Also, industry shift workers reported low levels of decision latitude compared to industry day workers, which is all in line with earlier studies (37,38). Even after excluding employees with a high educational level from the industry population, the distribution of educational level differed among shift and day workers.…”
Section: Strengths and Limitationssupporting
confidence: 77%
“…Nevertheless, the descriptive results revealed that both industry and healthcare shift workers had a higher prevalence of emotionally and physically demanding work compared to day workers employed in the same sector. Also, industry shift workers reported low levels of decision latitude compared to industry day workers, which is all in line with earlier studies (37,38). Even after excluding employees with a high educational level from the industry population, the distribution of educational level differed among shift and day workers.…”
Section: Strengths and Limitationssupporting
confidence: 77%
“…Despite previous reports suggesting that former shift workers and 2-shift workers may have an increased CVD risk (11,12), previous MetS studies have concentrated on rotating shift work and therefore there is need to assess the risk in diverse shift schedules. In the present study, we separated former shift workers from current day workers and designated in-flight workers, whose work schedules are highly irregular, as a separate study group.…”
Section: Shift Work and The Metabolic Syndromementioning
confidence: 89%
“…Tenkanen et al reanalysed data from Helsinki Heart Study. 22 Comparing all the shift workers with all the day workers and adjusting for age, they found an RR of 1.5 (95% CI 1.1-2.1). In line with our findings they saw a small decrease to 1.4 in RR when adjusting for lifestyle factors, Thirty one per cent of the study population was receiving treatment with gemfibrozil.…”
Section: Discussionmentioning
confidence: 99%